Injections and infections: understanding syringe service program utilization in a rural state - Kinna Thakarar; Nitysari Sankar; Kimberly Murray; Frances L. Lucas; Debra Burris; Robert P. Smith (BMC, 2021)
Abstract Background Increasing rates of injection drug use (IDU) associated-infections suggest significant syringe service program (SSP) underutilization. Our study objective was to assess practices of safe injection techniques and to determine predictors of SSP utilization in a rural state. Patients and methods This was a fifteen-month cross-sectional study of participants hospitalized with IDU-associated infections in Maine. Data were collected through Audio Computer-Assisted Self-Interview survey and medical record review. Descriptive analyses were performed to characterize demographics, health characteristics, and injection practices. The primary outcome was SSP utilization, and the main independent variable was self-reported distance to SSP. Logistic regression analyses were performed to identify factors associated SSP utilization, controlling for gender, homelessness, history of overdose, having a primary care physician and distance to SSP. Results Of the 101 study participants, 65 participants (64%) reported past 3 month SSP utilization, though only 33% used SSPs frequently. Many participants (57%) lived more than 10 miles from an SSP. Participants who lived less than 10 miles of an SSP were more likely to use an SSP (adjusted odds ratio 5.4; 95% CI 1.9-15.7). Conclusions Our study highlights unsafe injection practices and lack of frequent SSP utilization among people admitted with IDU-associated infections in a rural state. Especially given increasing stimulant use, these results also highlight the need for SSP access. Particularly in rural areas where patients may live more than 10 miles from an SSP, expansion of harm reduction services, including mobile units, should be a priority.